Question
upstudy study bank question image url

3 If \( \cos A=\frac{S}{6} \) and \( A+B-90^{\circ} \), use a sketch to find the value of \( \frac{\tan A \cdot \tan B \cdot \sin A}{\cos B} \). Prove the following identities: \( 4.1 \quad \cos ^{2} x+\sin x \cdot \cos x \cdot \tan x=1 \) \( 4.2 \frac{1-\tan ^{2} \theta}{1+\tan ^{2} \theta}=2 \cos ^{2} \theta-1 \) sinf 5 Simplify each of the following. osi \( 5.1 \frac{2 \sin \left(90^{\circ}-x\right)-\cos \left(360^{\circ}-x\right)}{2 \cos \left(90^{\circ}+x\right)-\sin \left(180^{\circ}+x\right)} \) e \( 5.2 \frac{\tan \left(180^{\circ}-x\right) \tan 45^{\circ} \cdot \cos (-x)}{\sin \left(180^{\circ}-x\right)} \)

Ask by Clark Burgess. in South Africa
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. The value of \( \frac{\tan A \cdot \tan B \cdot \sin A}{\cos B} \) is **1**. 2. The identity \( \cos^2 x + \sin x \cdot \cos x \cdot \tan x = 1 \) is proven. 3. The identity \( \frac{1 - \tan^2 \theta}{1 + \tan^2 \theta} = 2 \cos^2 \theta - 1 \) is proven. 4. Expression 5.1 simplifies to \( -\cot x \). 5. Expression 5.2 simplifies to \( -1 \).

Solution

Let's break down the problem step by step. ### Part 1: Finding \( \frac{\tan A \cdot \tan B \cdot \sin A}{\cos B} \) Given: - \( \cos A = \frac{S}{6} \) - \( A + B = 90^\circ \) (which implies \( B = 90^\circ - A \)) From the identity \( \tan B = \frac{\sin B}{\cos B} \) and using the co-function identity, we have: \[ \tan B = \cot A = \frac{1}{\tan A} \] Now, we can express \( \sin A \) and \( \cos B \): - \( \sin A = \sqrt{1 - \cos^2 A} = \sqrt{1 - \left(\frac{S}{6}\right)^2} \) - \( \cos B = \sin A \) Now substituting these into the expression: \[ \frac{\tan A \cdot \tan B \cdot \sin A}{\cos B} = \frac{\tan A \cdot \frac{1}{\tan A} \cdot \sin A}{\sin A} \] This simplifies to: \[ \frac{\sin A}{\sin A} = 1 \] ### Part 2: Proving the identities #### Identity 4.1: \( \cos^2 x + \sin x \cdot \cos x \cdot \tan x = 1 \) Starting with the left-hand side: \[ \cos^2 x + \sin x \cdot \cos x \cdot \tan x \] Substituting \( \tan x = \frac{\sin x}{\cos x} \): \[ = \cos^2 x + \sin x \cdot \cos x \cdot \frac{\sin x}{\cos x} \] This simplifies to: \[ = \cos^2 x + \sin^2 x \] Using the Pythagorean identity \( \sin^2 x + \cos^2 x = 1 \): \[ = 1 \] Thus, the identity is proven. #### Identity 4.2: \( \frac{1 - \tan^2 \theta}{1 + \tan^2 \theta} = 2 \cos^2 \theta - 1 \) Starting with the left-hand side: \[ \frac{1 - \tan^2 \theta}{1 + \tan^2 \theta} \] Substituting \( \tan^2 \theta = \frac{\sin^2 \theta}{\cos^2 \theta} \): \[ = \frac{1 - \frac{\sin^2 \theta}{\cos^2 \theta}}{1 + \frac{\sin^2 \theta}{\cos^2 \theta}} = \frac{\frac{\cos^2 \theta - \sin^2 \theta}{\cos^2 \theta}}{\frac{\cos^2 \theta + \sin^2 \theta}{\cos^2 \theta}} = \frac{\cos^2 \theta - \sin^2 \theta}{\cos^2 \theta + \sin^2 \theta} \] Using the Pythagorean identity \( \cos^2 \theta + \sin^2 \theta = 1 \): \[ = \cos^2 \theta - \sin^2 \theta \] Using the double angle identity \( \cos(2\theta) = \cos^2 \theta - \sin^2 \theta \): \[ = \cos(2\theta) \] Now, using the identity \( \cos(2\theta) = 2\cos^2 \theta - 1 \): \[ = 2\cos^2 \theta - 1 \] Thus, the identity is proven. ### Part 3: Simplifying the expressions #### Expression 5.1: \[ \frac{2 \sin(90^\circ - x) - \cos(360^\circ - x)}{2 \cos(90^\circ + x) - \sin(180^\circ + x)} \] Using the co-function identities: - \( \sin(90^\circ - x) = \cos x \) - \( \cos(360^\circ - x) = \cos x \) - \( \cos(90^\circ + x) = -\sin x \) - \( \sin(180^\circ + x) = -\sin x \) Substituting these into the expression: \[ = \frac{2 \cos x - \cos x}{2(-\sin x) - (-\sin x)} = \frac{\cos x}{-2\sin x + \sin x} = \frac{\cos x}{-\sin x} = -\cot x \] #### Expression 5.2: \[ \frac{\tan(180^\circ - x) \tan 45^\circ \cdot \cos(-x)}{\sin(180^\circ - x)} \] Using the identities: - \( \tan(180^\circ - x) = -\tan x \) - \( \tan 45^\circ = 1 \) - \( \cos(-x) = \cos x \) - \( \sin(180^\circ - x) = \sin x \) Substituting these into the expression: \[ = \frac{-\tan x \cdot 1 \cdot \cos x}{\sin x} = -\frac{\tan x \cdot \cos x}{\sin x} = -\frac{\sin x}{\sin x} = -1 \] ### Final Answers: 1. \( \frac{\tan A \cdot \tan B \cdot \sin A}{\cos B} = 1 \) 2. Identity 4.1 is proven. 3. Identity 4.2 is proven. 4. Expression 5.1 simplifies to \( -\cot x \). 5. Expression 5.2 simplifies to \( -1 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the value of \( \frac{\tan A \cdot \tan B \cdot \sin A}{\cos B} \) given that \( \cos A = \frac{S}{6} \) and \( A + B = 90^\circ \), you can use the relationships from trigonometric identities. Given that \( B = 90^\circ - A \), we have \( \tan B = \cot A \). Thus, \( \frac{\tan A \cdot \tan B \cdot \sin A}{\cos B} = \frac{\tan A \cdot \cot A \cdot \sin A}{\cos(90^\circ - A)} = \frac{\sin A}{\sin A} = 1 \). Now, let's tackle the identities: 1. For \( \cos^2 x + \sin x \cdot \cos x \cdot \tan x = 1 \), we can rewrite \( \tan x \) as \( \frac{\sin x}{\cos x} \), yielding \( \cos^2 x + \sin x \cdot \cos x \cdot \frac{\sin x}{\cos x} = \cos^2 x + \sin^2 x = 1 \), proving the identity. 2. Next, for \( \frac{1 - \tan^2 \theta}{1 + \tan^2 \theta} = 2 \cos^2 \theta - 1 \), we know \( \tan^2 \theta = \frac{\sin^2 \theta}{\cos^2 \theta} \). Replacing and simplifying yields \( 2\cos^2 \theta - 1 \), confirming the identity. Lastly, for simplification: 5.1: Simplifying \( \frac{2 \sin(90^\circ - x) - \cos(360^\circ - x)}{2 \cos(90^\circ + x) - \sin(180^\circ + x)} \) yields \( \frac{2 \cos x - \cos x}{-2 \sin x + \sin x} \) leading to \( \frac{1}{- \sin x} = -\csc x \). 5.2: The expression \( \frac{\tan(180^\circ - x) \tan 45^\circ \cdot \cos(-x)}{\sin(180^\circ - x)} \) simplifies to \( \frac{-\tan x \cdot 1 \cdot \cos x}{\sin x} = -\cot x \).

Related Questions

8. Simplify without using a calculator. (8.1) \( \frac{\sin \left(180^{\circ}-x\right) \cdot \tan \left(360^{\circ}-x\right)}{\cos \left(80^{\circ}-x\right)} \times \frac{\cos \left(-180^{\circ}-x\right)}{\cos \left(360^{\circ}+x\right) \sin \left(360^{\circ}-x\right)} \) \( 8.2 \frac{\cos 135^{\circ} \sin 160^{\circ}}{\sin 225^{\circ} \cos 70^{\circ}} \) (8.3) \( \frac{\sin (-\theta)+\cos 120^{\circ}+\tan \left(-180^{\circ}-\theta\right)}{\sin ^{2} 225^{\circ}-\tan (-\theta)-\cos \left(90^{\circ}+\theta\right)} \) B.4 \( 4^{x} \frac{\sin 247^{\circ} \cdot \tan 23^{\circ} \cdot \cos 113^{\circ}}{\sin \left(-157^{\circ}\right)} \) (8.5) \( \frac{3 \cos 150^{\circ} \cdot \sin 270^{\circ}}{\tan \left(-45^{\circ}\right) \cdot \cos 600^{\circ}} \) 8.6) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}+x\right)}{\sin (-x)}-\sin y \cdot \cos \left(90^{\circ}-y\right) \) \( 8.7 \frac{\tan 30^{\circ} \cdot \sin 60^{\circ} \cdot \cos 25^{\circ}}{\cos 135^{\circ} \cdot \sin \left(-45^{\circ}\right) \cdot \sin 65^{\circ}} \) 6.8) \( \frac{\tan \left(180^{\circ}-x\right) \cdot \sin \left(90^{\circ}-x\right)}{\cos \left(90^{\circ}+x\right)}-\frac{\cos \left(180^{\circ}-x\right)}{\sin \left(90^{\circ}+x\right)} \) \( 8.9 \frac{\sin 189^{\circ}}{\tan 549^{\circ}}-\frac{\cos ^{2}\left(-9^{\circ}\right)}{\sin 99^{\circ}} \) Solving trigonometric equations (no calculators) (1.) If \( \sin \mathrm{A}=\frac{-3}{5} \) and \( 0^{\circ}<\mathrm{A}<270^{\circ} \) determine the value of: \( 1.1 \cos A \) \( 1.2 \tan A \). (2.) If \( -5 \tan \theta-3=0 \) and \( \sin \theta<0 \), determine: \( 2.1 \sin ^{2} \theta^{\circ} \) \( 2.25 \cos \theta \) \( 2.3 \quad 1-\cos ^{2} \theta \) 3. If \( 13 \cos \theta+12=0 \) and \( 180^{\circ}<\theta<360^{\circ} \), evaluate: \( 3.2 \tan \theta \) \( 3.1 \sin \theta \cos \theta \) \( 3.3 \sin ^{2} \theta+\cos ^{2} \theta \). (4.) If \( 3 \tan \theta-2=0 \) and \( \theta \in\left[90^{\circ} ; 360^{\circ}\right] \), determine, the value of \( \sqrt{13}(\sin \theta-\cos \theta \) (5.) If \( \cos 52^{\circ}=k \) as illustrated in the diagram, determine each of the following i
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy